2013
DOI: 10.1590/s0102-33062013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Germination and sporophytic development of Regnellidium diphyllum Lindm. (Marsileaceae) in the presence of copper

Abstract: Regnellidium diphyllum Lindm. is a heterosporous fern growing in wetlands and humid soils that are being converted to agricultural activities. Many products that are used in agriculture contain copper, resulting in surface and groundwater contamination. Germination and initial development tests were performed using Meyer's solution containing copper sulphate at concentrations of 0 (control), 1, 5, 10, 50 and 100 mg L −1 . Th e experiment was conducted in a growth chamber at 25 ± 1°C for 28 days, with a 12/12-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…While copper is required in minimal amounts for both plants and animals, its excessive concentration may be hazardous. Copper concentrations over a certain level may result in stunted development and chlorosis [65]. Although chromium is neither needed nor useful for plants, it is necessary for trace amounts for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…While copper is required in minimal amounts for both plants and animals, its excessive concentration may be hazardous. Copper concentrations over a certain level may result in stunted development and chlorosis [65]. Although chromium is neither needed nor useful for plants, it is necessary for trace amounts for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing concentrations of nickel (0.05 to 100 mg L -1 ) were also associated with a decrease in germination percentage from 75 to 45% (Kieling-Rubio et al, 2012). Lower germination percentages (of approximately 49%) were also observed in megaspores exposed to 50 mg L -1 copper (Cassanego et al, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…The length of roots, primary and secondary leaves was also shorter in sporophytes exposed to nickel concentrations of 3.2 and 4.8 mg L -1 than in sporophytes not exposed to nickel (Kieling-Rubio et al, 2012). Cassanego et al (2013) observed significant negative effects on the development of R. diphyllum sporophytes grown in media with copper concentrations of 5 mg L -1 and higher. The visible symptoms of root necrosis in cultures exposed to higher concentrations of lead can be at least partially explained by the excess of lead in the nutrient medium, which can lead to reduction in plant growth, inhibition of photosynthesis, cell injury and tissue necrosis, and might even be lethal (Sharma and Dubey, 2005).…”
Section: +mentioning
confidence: 76%
See 1 more Smart Citation
“…Fabaceae with up to 450 mg kg -1 of Cu added to the soil. Plants submitted to high doses of Cu may show shoot chlorosis (Yruela, 2013), early defoliation, and reduced shoot (Grassi Filho, 2005;Cassanego et al, 2013) and plant growth (Gautam et al, 2016). However, Steffen et al (2012) showed that the application of both the isolate UFSC-PT116 and eucalyptus essential oil increases the development of the aerial part of Caesalpinia peltophoroides Benth.…”
Section: Resultsmentioning
confidence: 99%